Research on Acetylene Sensing Properties and Mechanism of SnO2 Based Chemical Gas Sensor Decorated with Sm2O3 - Qu Zhou; Meiqing Cao; Wude Li; Chao Tang; Shiping Zhu (Journal of Nanotechnology)
Acetylene C2H2 gas is one of the most important fault characteristic hydrocarbon gases dissolved in oil immersed power transformer oil. This paper reports the successful preparation and characterization of samarium oxide Sm2O3 decorated tin oxide SnO2 based sensors with hierarchical rod structure for C2H2 gas detection. Pure and Sm2O3 decorated SnO2 sensing structures were synthesized by a facile hydrothermal method and characterized by XRD, FESEM, TEM, EDS, and XPS measurements, respectively. Planar chemical gas sensors with the synthesis samples were fabricated, and their sensing performances to C2H2 gas were systematically performed and automatically recorded by a CGS-1 TP intelligent gas sensing analysis system. The optimum operating temperature of the Sm2O3 decorated SnO2 based sensor towards 50 μL/L of C2H2 is 260°C, and its corresponding response value is 38.12, which is 6 times larger than the pure one. Its response time is about 8–10 s and 10–13 s for recovery time. Meanwhile good stability and reproducibility of the decorated sensor to C2H2 gas are also obtained. Furthermore, the proposed sensor exhibits excellent C2H2 selectivity among some potential interface gases, like H2 and CO gas. All sensing results indicate the sensor fabricated with oxide Sm2O3 decorated SnO2 nanorods might be a promising candidate for C2H2 detection in practice.